Influence of fetal sex on perinatal outcomes in women with gestational diabetes mellitus. Issue 3 (6th December 2019) - Hu, Jun; Ge, Zhijuan; Xu, Qianyue; Shen, Shanmei; Wang, Yanmei; Zhu, Dalong; Bi, Yan
Abstract: Background: Fetal sex has recently been considered to be related to maternal glucose homeostasis and perinatal outcomes during pregnancy. Here, we investigated the effects of fetal sex on the perinatal outcomes of pregnancies with normal glucose tolerance (NGT) and gestational diabetes mellitus (GDM). Methods: This was a retrospective cohort study of 1292 women with NGT and 1155 women with GDM. Pregnant women were divided into four groups according to the maternal glucose level and fetal sex. Logistic regression was used to evaluate the risks for adverse perinatal outcomes among NGT‐males, NGT‐females, GDM‐males and GDM‐females. Results: NGT‐males had higher risks for macrosomia and large for gestational age (LGA) than NGT‐females with an odds ratio (OR) of 1.9 (95% CI 1.2‐2.9). Additionally, GDM‐males had higher risks for neonatal infection (OR, 3.0; 95% CI, 1.3‐6.9), acute respiratory disorders (OR, 3.9; 95% CI, 1.1‐13.7) and abnormal neonatal central nervous system development (OR, 3.1; 95% CI, 1.1‐8.4) than GDM‐females. Furthermore, there was a significantly higher risk for newborn infection (OR, 8.5; 95% CI, 1.1‐66.8) in the GDM‐male group than in the GDM‐female group with a glycosylated hemoglobin A1c (HbA1c) level ≥5.5% in the late trimester of pregnancy, which was not observed with an HbA1c level of <5.5%. Conclusions: Male fetuses have worse perinatal outcomes than female fetuses, and the difference is more pronounced in GDM pregnancies. More postpartum care is needed for male fetuses, especially in GDM pregnancies with substandard glycemic control.